2020
DOI: 10.1177/0361198120911053
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Automobile Mode Share in Understanding the Full Impact of Urban Form on Work-Based Vehicle Distance Traveled

Abstract: Vehicle kilometers traveled (VKT) has been widely used in regional planning as a key sustainability performance indicator. Many regional growth plans for reducing work trip VKT have been proposed, with a focus on land use development in employment centers. Despite the potential impact of urban form on the reduction of VKT, the fundamentals of how this takes place remain unclear. This study analyzes the relationship between urban form, VKT, and mode shares by examining office commuting patterns in the Greater T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…An elevated rapid transit line provided extended access to the subway to the western side of Scarborough until August 2023 (5 stations in red, Figure 1), upon which time it was decommissioned absent any higher-order rapid transit alternative. A rapid transit busway will replace the subway by 2027 until the extension of the Line 2 subway arrives in Scarborough in 2030 (TTC, 2024), deepening their existing transit accessibility in the past 25 years (Allen & Farber, 2020).…”
Section: Case Study: Scarborough Canadamentioning
confidence: 99%
See 1 more Smart Citation
“…An elevated rapid transit line provided extended access to the subway to the western side of Scarborough until August 2023 (5 stations in red, Figure 1), upon which time it was decommissioned absent any higher-order rapid transit alternative. A rapid transit busway will replace the subway by 2027 until the extension of the Line 2 subway arrives in Scarborough in 2030 (TTC, 2024), deepening their existing transit accessibility in the past 25 years (Allen & Farber, 2020).…”
Section: Case Study: Scarborough Canadamentioning
confidence: 99%
“…While this is partly an outcome of the specific vehicle and fuel technologies used in transportation, it is also an outcome of the automobile-dependent urban context in which individuals, households, employment, and other activity destinations are located. Previous research has found that low-density and single-use neighbourhoods are associated with less frequent transit use and greater vehicle kilometres travelled by private automobiles (Cervero & Kockelman, 1997;Ewing & Cervero, 2010;Xi et al, 2020). Some have called for a "retrofitting" of the built form of the suburbs to become more dense, mixed-use, walkable, and transit-supportive (Cervero et al, 2017;Dunham-Jones & Williamson, 2008;Talen, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…They have also both undergone polycentric development over the past several decades, with urban centres emerging in more suburban locations (Sarkar, Wu, & Levinson, 2020). These suburban centres however tend to have fewer transit connections and are typically reached more via car than public transit, compared to their historical cores (Xi, Allen, Miller, Farber, & Keel, 2020).…”
Section: Regional Contextmentioning
confidence: 99%
“…The dependent variable, transit mode share in a zone, is a percentage (bounded by 0 and 1), so we utilize generalized linear regression with a logit link function. The same type of model has been used in previous studies predicting neighbourhood-level transit mode share (Moniruzzaman & Páez, 2012;Xi et al, 2020). Our models are also weighted by the population in each zone.…”
Section: Immigrant Settlement and Transit Mode Sharementioning
confidence: 99%